2009
DOI: 10.1051/radiopro/20095064
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends and explanation for airborne137Cs activity level increases in France

Abstract: Abstract.Airborne 137 Cs level in France is not decreasing significantly anymore (mean yearly value around 0,25 Bq.m −3 ) contrarily to what was noticed in the past decades. This observation points out the role of processes that delay the atmospheric cleaning and participate to the persistence of radionuclide in the air at ground-level after a deposit, in the frame of medium as well as long-dated post-accidental contexts. The current background level also yields to consider 137 Cs in the atmosphere as a trace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…(i) Local re-suspension of 137 Cs from soil (Pham et al, 2011;Sýkora et al, 2012); (ii) 137 Cs input from Saharan dust events (Masson et al, 2010;Pham et al, 2005Pham et al, , 2011; (iii) Contributions from field/forest fires burning biota containing 137 Cs of the Chernobyl and global fallout origin (Wotawa et al, 2006;Masson et al, 2009;Hirose and Povinec, 2015). Menut et al (2009) showed that in the case of the 21e22 February 2004 Saharan dust event, the main part (80%) of the dust found in southern France was from the eastern Maghreb region.…”
Section: Anthropogenic Radionuclidesmentioning
confidence: 99%
See 1 more Smart Citation
“…(i) Local re-suspension of 137 Cs from soil (Pham et al, 2011;Sýkora et al, 2012); (ii) 137 Cs input from Saharan dust events (Masson et al, 2010;Pham et al, 2005Pham et al, , 2011; (iii) Contributions from field/forest fires burning biota containing 137 Cs of the Chernobyl and global fallout origin (Wotawa et al, 2006;Masson et al, 2009;Hirose and Povinec, 2015). Menut et al (2009) showed that in the case of the 21e22 February 2004 Saharan dust event, the main part (80%) of the dust found in southern France was from the eastern Maghreb region.…”
Section: Anthropogenic Radionuclidesmentioning
confidence: 99%
“…Povinec, 2000, 2002). Radionuclides in the atmosphere rapidly attach on submicron-sized aerosols, and their variability in ground-level air is driven by the behavior of aerosols (Masson et al, 2009;Sýkora et al, 2012;Povinec et al, 2012;Hirose and Povinec, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The 137 Cs in the terrestrial environment is present in atmospheric aerosols, soil and vegetation. It has been used worldwide as a tracer of environmental processes, specifically for studying transport processes in atmospheric, aquatic and terrestrial ecosystems (Lee et al, 2002;Igarashi et al, 2005;Pham et al, 2005Pham et al, , 2011Lujaniené et al, 2006Lujaniené et al, , 2009Masson et al, 2009). Because of relatively easy analytical methodologies, it has been monitored in the atmosphere since the beginning of the 1960's.…”
Section: Introductionmentioning
confidence: 98%
“…Periodic atmospheric radioactivity monitoring performed at several western European countries detected 137 Cs peaks in surface air in the summer of 2002 and afterwards (Masson et al, 2008). In the absence of known accidental radioactivity releases, it was interpreted as re-suspension by summer fires of the 137 Cs from Chernobyl accident deposited in Ukraine and Belorussia forests and soils (Amiro et al, 1996;Paatero et al, 2009).…”
Section: Introductionmentioning
confidence: 99%